1985
DOI: 10.1136/bmj.291.6506.1424-d
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of Iodosorb.

Abstract: resonance. The guidelines for magnetic resonance imaging in Britain laid down by the National Radiological Protection Board allow for studies during the second and third trimesters of pregnancy. Smith has reported his findings in 120 normal and abnormal pregnancies (Smith F W, presented at fourth annual meeting of Society of Magnetic Resonance in Medicine, 1985). After 26 weeks, gestation he found that the fetal head, brain, eyes, lungs, heart, liver, bladder, and limbs were routinely seen. In normal pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Nine RCTs across both VLU and PU indications identified a reduction in purulence and cellular debris after use 9‐12,15,16,25‐27 . Significant reductions in pus and cellular debris following 4 weeks of treatment with CIOD vs SOC were demonstrated in VLUs by Lindsay 10 ( P < .002) and Troeng 9 ( P < .005)—with significant reductions observed at also weeks 2 and 6 in the latter study ( P < .025/ P < .001).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Nine RCTs across both VLU and PU indications identified a reduction in purulence and cellular debris after use 9‐12,15,16,25‐27 . Significant reductions in pus and cellular debris following 4 weeks of treatment with CIOD vs SOC were demonstrated in VLUs by Lindsay 10 ( P < .002) and Troeng 9 ( P < .005)—with significant reductions observed at also weeks 2 and 6 in the latter study ( P < .025/ P < .001).…”
Section: Resultsmentioning
confidence: 92%
“…Several studies involving participants with VLU, DFU, and PU reported complete wound healing following CIOD intervention. In VLUs, significantly more wounds were healed using CIOD compared to SOC across studies spanning 6 weeks, 26,29 8 weeks, 10,25 and 12 weeks 12,13 intervention. Likewise in PUs, significantly more healing events were reported in the CIOD group compared to SOC in an RCT by Moberg et al 16 Also, in an open controlled comparative study in DFU, more wounds in the CIOD group healed compared to the SOC comparison group (5/22 vs 2/19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CI has long been used effectively in chronic wounds and is supported by many clinical studies demonstrating the removal of barriers to healing, such as microbial infection, slough/debris, and exudate . In addition, a recent meta‐analysis (Cochrane review) highlighted that CI generates higher healing rates than standard care in venous leg ulcers (VLUs) …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] CI has long been used effectively in chronic wounds and is supported by many clinical studies demonstrating the removal of barriers to healing, such as microbial infection, 21,[24][25][26][27] slough/debris, 21,[28][29][30][31][32] and exudate. 21,24,27,28,31,33,34 In addition, a recent meta-analysis (Cochrane review) highlighted that CI generates higher healing rates than standard care in venous leg ulcers (VLUs). 35,36 CI has previously been demonstrated to be highly effective against mature biofilms in multiple in vitro models incorporating various conditions, such as low and high exudate, 37 clinically relevant media, 38 or clinically relevant substrates such as porcine tissue.…”
mentioning
confidence: 99%